2019
DOI: 10.2196/14123
|View full text |Cite
|
Sign up to set email alerts
|

Types and Frequency of Infusion Pump Alarms and Infusion-Interruption to Infusion-Recovery Times for Critical Short Half-Life Infusions: Retrospective Data Analysis

Abstract: BackgroundAlarm fatigue commonly leads to a reduced response to alarms. Appropriate and timely response to intravenous pump alarms is crucial to infusion continuity. The difficulty of filtering out critical short half-life infusion alarms from nonurgent alarms is a key challenge for risk management for clinicians. Critical care areas provide ample opportunities for intravenous medication error with the frequent administration of high-alert, critical short half-life infusions that require rigorous maintenance f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 14 publications
1
16
0
4
Order By: Relevance
“…Long infusion interruptions are even more undesirable as medications that have a short half-life for effectiveness require rapid alarm resolution, imposing an additional time pressure on clinicians. 38 The findings of this work provide additional insights into the impact of smart infusion pump alerts and alarms on nursing workflows. Infusion alerts and alarms are mechanisms designed to aid medication administration by drawing caregivers' attention to issues that can potentially affect a patient's safety.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Long infusion interruptions are even more undesirable as medications that have a short half-life for effectiveness require rapid alarm resolution, imposing an additional time pressure on clinicians. 38 The findings of this work provide additional insights into the impact of smart infusion pump alerts and alarms on nursing workflows. Infusion alerts and alarms are mechanisms designed to aid medication administration by drawing caregivers' attention to issues that can potentially affect a patient's safety.…”
Section: Discussionmentioning
confidence: 87%
“…32,[35][36][37] One study identified the volume of infusion alarms specific to critical short half-life infusions to evaluate user response times to these alarms. 38 In another study, formal central infusion monitoring and environmental changes in a neonatal intensive care unit (NICU) were found to reduce alarm fatigue, improve reaction time, and improve preempting of avoidable alarms. 39 These efforts are critical in improving nursing workflows, patient safety, and overall health care delivery.…”
Section: Background and Significancementioning
confidence: 99%
“…Infusion of lowdose naloxone using an infusion pump may therefore help to improve patient outcomes while minimizing drug-related side effects. More recently, computer-based perfusion pumps have been developed to maximize the efficacy of drugs [16,17]. These measures make it possible to precisely control the overall doses of drugs administrated or to compare the predictive performance of such protocols which differ in either general approach.…”
Section: Discussionmentioning
confidence: 99%
“…Another challenge in IV therapy can be the beeping tone of infusion pumps, which may disturb patients and incur additional nurse visits to the patient room [ 11 , 12 ]. Although critical alarms are hard to filter from non-urgent ones [ 11 ], and the number of alarms has increased exponentially [ 12 ], intravenous pump alarms need to be responded to accurately and timely to maintain infusion continuity [ 11 ].…”
Section: Introductionmentioning
confidence: 99%